Nasogastric Tube Feeding for Individuals With Anorexia Nervosa: An Integrative Review. (November 2016) - Kells, Meredith; Kelly-Weeder, Susan
BACKGROUND: The use of nasogastric (NG) feeding in individuals with anorexia nervosa (AN) is endorsed by national professional organizations; however, no guidelines currently exist.OBJECTIVES: The objectives of this review were to identify and evaluate outcomes of NG feedings for individuals with AN and to develop recommendations for future research, policy, and practice.DESIGN: An integrative review of the research literature was conducted.RESULTS: Of the 19 studies reviewed, all indicated short-term weight gain following NG feeding. Four studies examined adherence; nearly 30% of subjects were nonadherent as evidenced by tube manipulation. Seven studies reported psychiatric outcomes, suggesting NG feeding reduces eating disorder behaviors but not overall symptomology.CONCLUSIONS: NG feeding promotes short-term weight gain; however, long-term outcomes are poorly understood. Future research, using rigorous methods, is still needed to inform practice.